Atitudes frente ao doente mental: correlatos valorativos e de traços de personalidade - Dantas, Gildevan Estrela (2014)
The history of madness exerts an important representation in the idealogic and practices change in the ways that refer to the better offer of assistence to mental sick. In this way are presented the revolutions wich describe important changes at the world level in the Psychiatristic treatment and its contributes to the Italian Revolution and its influence in the process that comes from Brazil, that resulted in the approval law 10.201/2001, of Psychiatric reform. Understanding the Psychiatry as an important piece of power in the strategy of control and the subjection/domination subject in suffering. Psychy it's new ways of to take care must be talked. As a result of these arguments the healthy models come trying to understand the mental sick beyond of the organic aspects as also the subjectives aspects of this. This transition of taking care must be evidenced by means of healthy models: biomedical and biopsychosocial. Considering this logic, we look for here to become important the mental sick as human possibility and its connection to the social order. In the way of this historical construction of the madness, this present dissertation had as a goal to know if the human values and their personality ways explain the attitudes in front of the mental sick. Considerating the human values as main guides of the human actions and being the personality below it. For to do this were done three close studies. The study 1: Had as a goal to construct and to valid a spare of attitudes front the mental sick. A group of two hundred students from healthy area took part in this study (medicine, nursing and psychology) from a public university and other private university from the city of João Pessoa PB. The students were divided for ages between seventeen to forty-nine years old (M 23.67 - DP 5.04. A EAFDM after checked in its expiry meaning and descriminating power (followed the two criteries from Faiser and Catell), was showed structured in two members: Authoritarism (α- 0,81) and benefiting (α 0.75). Thge two factors were explained together 20,8% of variation of the total. The study 2: for its turn, had as a goal to prove the factorial structure of EAFDM giving psychometric evidences stroger to the refered messurement. Counted sample of two hundred and three students with several ages between seventeen to fifty-two years old ( M 23.93 DP 5.54). The results of the factorial analyse confirmatory (AFC) permited to conprove the bifactorial structure of EAFDM, identificated in the study 1 showing indicators od adjust reliable compound satisfactory. To finish, were done the Study 3: Compounding the sample of two hundred and thirty students, professional from the healthy area. They answered to EAFDM questions of the basic values (QVB) The Big Five is a socialdemographic questionary. The analyse return (stepwise) ways to eleboration of a theoric model envolving the values of the under functions experimentation and interactive messuring the ways of personality consciousity and kindness, for its return explaining the attitudes front the madness sick in relation to the factor authoritarism. While the under functions experimentation , rule and interactive messuring the ways of neuroticism. In general, the model shows itself adjusted to the close details. Ending that is fundamental to develop projects with the healthy professionals specially, related to affectivity of public healthy politics to madness sick, and this way driven take back the citizenship of these people and bring them back to society.